Leveraging data and metadata for understanding interpersonal communication in adolescents: A study of Indonesian’s junior high schools students - Widyastuti, Dian Ari; Purwanta, Edi; Astuti, Budi; Barida, Muya; Nugraha, Ariadi; Khasanah, Ramadhani Uswatun (Edelweiss Applied Science and Technology, 2025)
Interpersonal communication is a crucial aspect of development during adolescence, particularly among junior high school students. Well-developed interpersonal communication can positively impact adolescents' lives. This study aims to explore the patterns of interpersonal communication among adolescents in Indonesia using data and metadata collected during the research. The exploration was conducted by comparing differences in interpersonal communication based on gender, age, and socio-economic status. This study employed a comparative research design. Data were collected using the interpersonal communication scale. The respondents in this study were 1,359 junior high school students in Indonesia, selected through simple random sampling. Data analysis was performed using ANOVA. The results of ANOVA indicate significant differences in adolescents' interpersonal communication based on gender, age, and socio-economic status. The findings of this study are expected to serve as a foundation for developing educational programs in schools, particularly in guidance and counseling services, to foster a generation of adolescents in the digital era who can build high-quality interpersonal relationships.